Six sigma / Deepali Kishor Desai. - Desai, Deepali Kishor (Himalaya Pub. House, 2010)
This book is developed for ambitious people who are driving their way towards improvement, efficiency, customer targeted business process. As the name suggest, book guides people to travel the Six Sigma way. First part consists of what Six Sigma, ways to Six Sigma, organizing working people and methods of Six Sigma. Whereas, second part guides to implement, use of Six Sigma tools, Six Sigma and top level management and live cases of success with Six Sigma.